A Study to Assess the Effectiveness of Role Play on Team Nursing among 2nd Year B.Sc. Nursing Students in Selected Nursing College Tirupati, AP, India (International Journal of Nursing Education, 2020)
The aim of the study was to assess the effectiveness of role play on team nursing among 2nd year B.Sc(N)students in CON, SVIMS, Tirupati.Objectives:•? To assess the level of knowledge on team nursing among 2nd year B.Sc (N) students in CON, SVIMS,Tirupati.•? To assess the effectiveness of role play among 2nd year B.Sc (N) students in CON, SVIMS, Tirupati.•? To find the correlation between level of knowledge and selected demographic variables of 2nd year B.Sc(N) studentsMethodology: By using convenient sampling technique a preexperimental research design was adopted,100 2nd year B.Sc.(N) students were choosen as samples, and data collection was done by using a selfstructured questionnaire.Results: The study results revealed that out of 100 samples 53% (53) had inadequate knowledge, 31%(31)had moderate knowledge, and 16%(16) had adequate knowledge in their pre test and the post test resultshad shown as 28%(28) had moderate knowledge, and 72%(72) had adequate knowledge, none of them hadinadequate knowledge.Conclusion: As the technology in nursing education has been increasing day by day; role play is one of thebest live innovative method of giving essential information to the students. In the present study the resultsshowed that, the role play was effectively improved the knowledge of 2nd year B.Sc(N) students regardingteam nursing.
Keywords: Role-Play, Team nursing, Effectiveness